2013
DOI: 10.1088/1367-2630/15/11/113038
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order spin noise statistics

Abstract: The optical spin noise spectroscopy (SNS) is a minimally invasive route toward obtaining dynamical information about electrons and atomic gases by measuring mesoscopic time-dependent spin fluctuations. Recent improvements of the sensitivity of SNS should make it possible to observe higher-order spin correlators at thermodynamic equilibrium. We develop theoretical methods to explore higher-order (third and fourth) cumulants of the spin noise in the frequency domain. We make predictions for the possible function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 50 publications
(81 reference statements)
4
36
0
Order By: Relevance
“…In general, only the full set of all correlators contains complete information about an interacting system. Higher-order correlations have been studied theoretically [51,52] and experimentally in magnetic systems such as spin glasses [5] and amorphous magnets [53], but we are not aware of any prior experimental studies of higherorder correlations of fluctuations in magnetic films in thermal equilibrium. Such correlators, however, play an important role in the theory of phase transitions and nonlinear thermodynamics [54].…”
Section: Higher-order Correlations Of the Magnetization Noisementioning
confidence: 99%
See 1 more Smart Citation
“…In general, only the full set of all correlators contains complete information about an interacting system. Higher-order correlations have been studied theoretically [51,52] and experimentally in magnetic systems such as spin glasses [5] and amorphous magnets [53], but we are not aware of any prior experimental studies of higherorder correlations of fluctuations in magnetic films in thermal equilibrium. Such correlators, however, play an important role in the theory of phase transitions and nonlinear thermodynamics [54].…”
Section: Higher-order Correlations Of the Magnetization Noisementioning
confidence: 99%
“…In general, magnetic systems can of course break time-reversal symmetry. However, Im[C 3 ] = 0 is expected to hold for Ising-Glauber spin dynamics that satisfy detailed balance at thermal equilibrium [51]. Figure 7 shows the real part of C 3 , measured at a location on the trilayer where m z (B z ) increases linearly (and the noise power S(ν) is large) when |B z | < B sat .…”
Section: Higher-order Correlations Of the Magnetization Noisementioning
confidence: 99%
“…The relative strength Q r defined in Eq. (32) has been originally introduced in Ref. [15] to minimize this dependency.…”
Section: B Spin-noise Power Spectrum C2(ω)mentioning
confidence: 99%
“…Yet, quadrupolar interactions play an important role in the understanding of the long-time decay of higher-order spin response functions [29][30][31] especially at large magnetic fields above 1T. Since those fourth-order spin correlation functions [29][30][31] have been investigated in the time domain, it has been suggested [32,33] to extend the conventional SNS to higher-order spin noise correlations. The third-order spin correlation * These two authors contributed equally.…”
Section: Introductionmentioning
confidence: 99%
“…[11] In addition, Li et al developed theoretical methods to explore higher-order (third and fourth) cumulants of the spin noise in the frequency domain. [12,13] A lot of works have been done both theoretically and experimentally to understand the spin noise. Oestreich et al did SNS measurements under resonant as well as non-resonant probing conditions in an inhomogeneously broadened optical system (Rb vapor with 1 mbar of He buffer gas), and found that the SNS signal amplitude depends not only on the coherence between the ground and the excited states, but also on the ground-ground and excited-excited coherences in resonant and qusi-resonant probing conditions.…”
Section: Introductionmentioning
confidence: 99%